Bit Error Probability of Vlc Systems in Underground Mining Channels with Imperfect Csi - Seguel-Gonzalez, F (Elsevier GmbH, 2022)
Analytical expressions of the statistical distribution of the underground mining visible light communication (UM-VLC) square-channel gain are derived considering scattering, shadowing, and a random position and orientation of the receiver. These expressions are employed to compute the system s bit error probability (BEP) considering shot and thermal noises, on–off keying modulation, as well as perfect and imperfect channel state information (CSI) at the receiver side. The results obtained for the BEP are validated by computer simulations for various UM-VLC scenarios. A close agreement is observed between the analytical and simulated curves. Furthermore, the performance of the UM-VLC system improves by increasing the field-of-view (FoV) and/or signal-to-noise-ratio. Indeed, for a FoV value of 45° for both the UM-VLC system with perfect CSI and imperfect CSI, the best performance in terms of BEP is obtained. In terms of the UM-VLC system with imperfect CSI, BEP curves saturate for higher values of signal-to-noise-ratio (SNR) due to lower values of FoV, specifically in the case of 45°. Finally, the performance of the UM-VLC system increases significantly for higher values of SNR, specifically in the case of 20 dB. © 2022 The Author(s)